2020
DOI: 10.2147/ijwh.s191200
|View full text |Cite
|
Sign up to set email alerts
|

<p>Vulvar Lichen Sclerosus: Current Perspectives</p>

Abstract: Vulvar lichen sclerosus (LS) is a chronic, inflammatory dermatosis that may lead to scarring of the vulva and sexual dysfunction. LS affects women of all ages and often goes unrecognized and underreported. Uncertainty continues to exist around its pathogenesis, histologic diagnosis, and treatment. However, there have been great advances in our understanding of autoimmunogenic targets in disease formation and progression. In addition, there has been recent investigation of potential non-steroid-based treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
36

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(203 citation statements)
references
References 79 publications
1
145
0
36
Order By: Relevance
“…A cohort study involving 27 women with symptomatic LS reported that 89% had complete regression of pruritus and pain after three or four fractioned CO 2 laser sessions 4-6 weeks apart ( 14 ). In addition, double-blind, randomized, placebo-controlled trials comparing fractional CO 2 laser with topical corticosteroid treatment for women with VLS are missing in the literature ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study involving 27 women with symptomatic LS reported that 89% had complete regression of pruritus and pain after three or four fractioned CO 2 laser sessions 4-6 weeks apart ( 14 ). In addition, double-blind, randomized, placebo-controlled trials comparing fractional CO 2 laser with topical corticosteroid treatment for women with VLS are missing in the literature ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we explored the absorption spectrum of the affected labia majora. For further analysis, 6×10 4 ROIs of a size of 1 × 1 pixel within the treatment areas of the labia majora of every patient were selected randomly. Figures 8C,F show the reflectance absorption curves of all selected ROIs for P 15 and P 19 .…”
Section: Effective Refmentioning
confidence: 99%
“…Vulvar Lichen Sclerosus (VLS) is a chronic mucocutaneous disorder, which is likely to lead to impairment in sexual function and the potential for malignant transformation [1][2][3][4]. Early diagnosis, prompt treatment, and appropriate follow-up are extremely important to prevent these negative sequelae [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…На данный момент опубликованы результаты ряда работ, показывающих положительные аспекты применения ФДТ с различными классами фотосенсибилизирующих агентов (в том числе 5-аминолевулиновая кислота и ее производные, хлориновые ФС и др.). Авторами исследований отмечена достаточно высокая частота полных клинических и морфологических регрессий при применении ФДТ у данных категорий пациенток [9][10][11][12][13][14][15].…”
Section: выводыunclassified